Esophageal atresia with or without tracheoesophageal fistula (EA/TEF): association of different EA/TEF subtypes with specific co-occurring congenital anomalies and implications for diagnostic workup - Bogs, Thomas Karl-Peter; Zwink, Nadine; Chonitzki, Vera; Hölscher, Alice; Boemers, Thomas M.; Muensterer, Oliver; Kurz, Ralf; Heydweiller, Andreas; Pauly, Marcus; Leutner, Andreas; Ure, Benno M.; Lacher, Martin; et al. (European journal of pediatric surgery, 2018)
Esophageal atresia with or without tracheoesophageal fistula (EA/TEF) represents the most common developmental malformation of the upper digestive tract. It is classified into six subtypes according to the classification of Vogt, depending on anatomical variation of this malformation. Around 50% of the patients with EA/TEF present additional anomalies, which often influence, next to the EA/TEF subtype, the overall prognosis of EA/TEF newborns. Here, we investigated the association of the different EA/TEF subtypes with co-occurring congenital anomalies in EA/TEF patients and demonstrate their implications for postnatal diagnostic workup.
Publikationsdatum: 06. Januar 2017 (online)
Gesehen am 20.04.2020